Research on the Energy Dissipation Patterns and Fragment Size Distribution Characteristics of Coal Under Cyclic Impact Loading With Confining Pressure - Yongliang, He; Yuping, Fu; Chuantian, Li; Liying, Sun; Dongya, Zhang (Geofluids, 2024)
This study examines energy dissipation patterns and failure mechanisms in coal under cyclic impact, crucial for preventing dynamic disasters like rock bursts and coal and gas outbursts. Using a 75‐mm split Hopkinson pressure bar (SHPB) experimental system, the dynamic mechanical characteristics and fragment size distribution patterns of coal samples were analysed under a confining pressure of 10 MPa, axial pressure of 12 MPa, and impact pressures of 0.25, 0.30, 0.35, 0.40, and 0.45 MPa for 1, 2, and 3 cycles. The experimental data indicate that as the number of impacts increases, the energy reflected by the coal samples gradually increases, while the transmitted energy correspondingly decreases. The energy absorbed per unit volume of the coal samples under the first, second, and third dynamic loading cycles and confining pressure is 0.56, 0.61, and 0.66 J/cm 3 , respectively, with energy absorption rates ranging from 16.2% to 33.8%. Under different impact pressures, the fractal dimension of coal fragmentation shows a linear change, and as the impact pressure increases, the degree of fragmentation intensifies, and the mass of the fragmented coal decreases. The strength reduction in the energy dissipation patterns of coal samples under dynamic loading provides important theoretical support for the prevention of rock bursts during coal mining.